Penggunaan Robot/Alat Bantu Seks dalam Perspektif Hukum Islam - Nobillah Muhammad Al Afghoni (An Nahdhoh Jurnal Kajian Islam Aswaja, 2022)
Islam as a religion that is rahmatan lil 'alamin has regulated and provided solutions so that the distribution of sexual desires between men and women becomes more beautiful, clean, holy, lawful, and falls into the category of worship, namely through the process of marriage. Islam recognizes that humans have a very great desire to have sex. Therefore, Islamic law regulates the distribution of these biological needs through marriage. By marriage, one can avoid adultery, because adultery can cause confusing offspring, crime against offspring, and family breakdown. It can even lead to the uprooting of family roots, causing infectious diseases and rampant moral depravity.